Socio-cultural factors influencing adolescent pregnancy in Ghana: a scoping review - Mustapha Amoadu; Edward Wilson Ansah; Patricia Assopiah; Philomina Acquah; Joyce Evelyn Ansah; Eunice Berchie; Doris Hagan; Elsie Amoah (BMC, 2022)
Abstract Background Adolescent pregnancy is a public health challenge that has well-defined causes, associated health risks, and social and economic consequences for adolescent, their families, communities, and society. The purpose of this scoping review is to summarize studies published on socio-cultural determinants of adolescent pregnancy in Ghana. Methods Search for records was done in four major databases, including PubMed CENTRAL, Science Direct and JSTOR. Records from Google and Google Scholar were also added, and results and findings from published and unpublished studies were included. All the 22 studies that met the eligibility criteria, were critically appraised. The guidelines for conducting scoping reviews by Arksey and O'Malley were followed. Results The result revealed that poverty, peer influence, low level of education, dysfunctional family, lack of communication between parents and their daughters, lack of sexual and reproductive health education, child marriage, coerced sex, misconception and non-usage of contraceptives, and decline in cultural values such as puberty rites and virginity inspection are some of the determinants of adolescent pregnancy in Ghana. The study also showed that there is a lack of high-quality observational studies that adjust for confounding variables. Conclusion Interventions and policies should be designed to take into consideration the needs, context, and background of adolescents. Programmes to enhance adolescent reproductive health need to consider multilevel factors such as person, family, community, institutions, national, and global issues that affect such programmes.